2003
DOI: 10.1046/j.1469-0691.2003.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Telithromycin 800 mg once daily for seven to ten days is an effective and well-tolerated treatment for community-acquired pneumonia

Abstract: An oral dose of telithromycin 800 mg once daily for seven to ten days is an effective and well-tolerated first-line treatment for mild to moderate CAP in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Our in-vitro results, with telithromycin, are also consistent with recent clinical data, which demonstrated excellent activity in the treatment of community-acquired pneumonia [26,27]. Based on the promising in vitro results in this study, clinical trials assessing the efficacy of the new respiratory tract quinolones and ketolides for the treatment of Legionnaire's disease due L. pneumophila and other species are indicated.…”
Section: Discussionsupporting
confidence: 89%
“…Our in-vitro results, with telithromycin, are also consistent with recent clinical data, which demonstrated excellent activity in the treatment of community-acquired pneumonia [26,27]. Based on the promising in vitro results in this study, clinical trials assessing the efficacy of the new respiratory tract quinolones and ketolides for the treatment of Legionnaire's disease due L. pneumophila and other species are indicated.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the present pooled analysis are consistent with the overall clinical and bacteriological efficacy (91.2 and 90.4%, respectively) observed in the trials of patients with CAP treated with a once-daily oral dose of telithromycin 800 mg [14,15,16,17,18,19,20]; Aventis,unpubl. data[].…”
Section: Discussionsupporting
confidence: 89%
“…Overall, azithromycin and the investigational ketolide cethromycin (ABT-773) are the most potent drugs against M. pneumoniae in terms of MICs (436). Recently published clinical trials evaluating the investigational ketolide telithromycin alone (57) or in comparison with the fluoroquinolone trovafloxacin (336) for treatment of pneumonia in adults demonstrated that this ketolide produced clinical cure rates of 100 and 93.3%, respectively, for persons whose infection was due to M. pneumoniae.…”
Section: Treatment Of Infections Due To M Pneumoniaementioning
confidence: 99%